Beyond salt tolerance: SOS1-13’s pivotal role in regulating the immune response to Fusarium oxysporum in Solanum phureja - Liang, Liqin; Liu, Xiaona; Guo, Liuyan; Wang, Liyan; Zhao, Yuehua; Wu, Yue; Chen, Yiqian; Liu, Weizhong; Gao, Gang (Frontiers in Plant Science, 2025)
IntroductionFusarium oxysporum (FOX) causes severe Fusarium wilt in the potato (Solanum tuberosum group Phureja) annually around the world. As an Na+/H+ antiporter, SOS1, a member of the salt oversensitive (SOS) signaling pathway plays important role in salt tolerance, but its function in plant disease resistance has been less studied.MethodsThe function of the potato SOS1 gene (StSOS1-13) responding to the FOX infection was researched by gain- and loss-of-function assays.ResultsStSOS1-13-overexpressed Arabidopsis differed from WT plants in multiple aspects post-FOX infection. It exhibited less ROS accumulation and cell necrosis in leaves, higher SOD and CAT activities accompanied by reduced MDA content, enhanced root development, increased tolerance to FOX infection, and an accelerated leaf stomatal closure rate along with a reduced stomatal aperture area. Additionally, the ectopic overexpression of StSOS1-13 in Arabidopsis induced down-regulation of AtPR12. Conversely, silencing the ortholog gene NbSOS1-13 in Nicotiana benthamiana showed more accumulation of ROS, serious cell necrosis, reduced activities of SOD and CAT, significantly increased MDA level, obvious leaf wilting, decreased tolerance to infection, and reduced leaf stomatal closure rate and accelerated stomatal area. Furthermore, the expression of SA and JA response-related genes (NbPR5 and NbPR12) was up-regulated in NbSOS1-13-silenced plants.DiscussionThese findings suggest that StSOS1-13 may serve as a key hub in the immune response to FOX infection by enhancing the antioxidant defense system, promoting root development to improve water uptake, facilitating leaf stomatal closure to minimize water loss through evaporation, and associating with the SA and JA signaling pathways.